JOURNEY TO EXCELLENCE: REVEALING THE IMPACT OF WORK EXPERIENCE ON THE PERFORMANCE OF PT TRI KEESON UTAMA PRODUCTION DEPARTMENT EMPLOYEES - Ipa Hafsiah Yakin (SEAN Institute, 2023)
This research aims to reveal the impact of work experience on employee performance in the Production Department of PT Tri Keeson Utama. The research method used is descriptive-associative with a quantitative approach. The research sample involved 38 employees from various positions in the production department. The research instrument is a questionnaire that measures employee work experience and performance. The results of data analysis using the t test showed that there was a significant relationship between work experience and employee performance (p < 0.05). These findings confirm that the higher the level of work experience, the higher the level of employee performance. The implication of this research is the importance of companies recognizing the value of work experience in improving employee performance and designing appropriate employee development strategies. By understanding the relationship between work experience and employee performance, companies can improve operational efficiency and ensure sustainable growth for employees and the organization as a whole.